Empowerment of Business Group Household of Bandeng Fishbone Stick Snack in Segoro Tambak, Sedati Sidoarjo - D. Hertati; Nurhadi; A. Kriswibowo (Nusantara Science and Technology Proceedings)
Coastal communities, both fishermen, cultivators, processors and fish traders, have complex problems, namely social, economic, educational problems. Empowerment of business groups is seen as one of the specific strategies to improve the ability and potential of coastal women to become more independent. Priority issues faced by coastal women in Segoro Tambak Village in producing Milkfish Fish Thorn Stack Snack are: 1) Limited knowledge and skills of coastal women in milkfish Stik Snack production techniques, 2) limited market access for business groups. So that a third party is needed to help improve production capabilities and support marketing success. Based on the partner's problems, this activity resulted in: the training on milkfish steak production in the form of counseling and practice provided by the extension team. Directives given by the extension team are related to the problem of the marketing method of milkfish steak. The existing condition of the home industry processed product marketing network looks very simple, namely, the producers directly market their processed products to food stalls and small shops or consumers can buy directly or order directly from the producers. The weakness of the marketing model is that the marketing range is very limited and lack of supervision in terms of product hygiene, taste, price stability, packaging, and in terms of promotion; because the model only relies on word of mouth promotion, so that the marketing network is less than the maximum resulting in no increase in production. there is an opportunity for mothers of coastal women's groups in the village of Segoro Tambak, Sedati, Sidoarjo to expand the range of the promotion and marketing of milkfish sticks or other processed home industry products, in order to get a larger number of consumers, compared to using marketing strategies traditional.